Antimicrobial resistance to colistin in neonates: epidemiological insights and public health implications in Nigeria – a mini review - Adewunmi Akingbola; Abiodun Christopher Adegbesan; Olaoluwa Olorunfemi; Kolade Adegoke; Kehinde Abereoje; Olajumoke Adewole; Victor Olamide Oluwasola; Somadila Igboanugo; Ademola Aiyenuro (Annals of Medicine)
Introduction/Background Antimicrobial resistance (AMR) remains a critical global health issue, particularly in low- and middle-income countries like Nigeria. Colistin, a last-resort antibiotic for multidrug-resistant Gram-negative infections, has seen rising resistance, posing a significant challenge for neonatal sepsis management. This narrative review focuses on colistin resistance in neonates in Nigeria, addressing a critical public health threat. With rising antimicrobial resistance, understanding its epidemiology in vulnerable populations is essential for effective interventions.Methods A narrative mini-review was conducted, focusing on literature, systematic reviews, and global and national reports on colistin resistance in neonates. Data were synthesized from studies across Africa, with an emphasis on epidemiological insights and implications for public health in Nigeria.Results The review identified an increasing trend of colistin resistance in Gram-negative bacteria in neonates across Nigeria. Key findings highlight the presence of mobile colistin resistance (MCR) genes, such as mcr-1, in clinical isolates from neonates, despite limited exposure to colistin. The analysis also emphasized the limitations in screening practices and gaps in neonatal AMR surveillance in Nigeria. The results suggest that inadequate antimicrobial stewardship, overuse of antibiotics, and poor healthcare infrastructure contribute to the rapid emergence of colistin resistance in neonates.Conclusion Colistin resistance in neonates poses a grave threat to public health. Addressing this issue requires urgent improvements in antimicrobial stewardship, neonatal care, and AMR surveillance systems. Strengthening laboratory capacities, improving infection prevention practices, and global cooperation are critical to mitigating the spread of colistin-resistant infections in neonates and reducing mortality in low-resource settings.